Vedolizumab as Induction and Maintenance Therapy for Crohn's Disease in Patients Naïve to or Who Have Failed Tumor Necrosis Factor Antagonist Therapy - Sands, Bruce E; Sandborn, William J; Van Assche, Gert; Lukas, Milan; Xu, Jing; James, Alexandra; Abhyankar, Brihad; Lasch, Karen (Inflammatory bowel diseases, 2017)
BACKGROUND: Vedolizumab is a gut-selective α4β7 integrin antagonist for the treatment of moderately to severely active Crohn's disease (CD). Aims of this study were to characterize the efficacy and safety of vedolizumab induction and maintenance therapy in patients who were naïve to tumor necrosis factor-alpha (TNF-α) antagonist therapy (TNF-naïve) or who had discontinued TNF-α antagonist therapy because of inadequate response (i.e., primary nonresponse), loss of response, or intolerance (collectively classified as the TNF-failure population). METHODS: Post hoc analyses of the efficacy data for 516 TNF-naïve and 960 TNF-failure patients from the GEMINI 2 and GEMINI 3 trials were evaluated at weeks 6, 10, and 52 and included clinical remission (CD Activity Index [CDAI] score ≤150), enhanced clinical response (≥100-point decrease from baseline in CDAI score), durable clinical remission (remission at ≥80% of visits), and corticosteroid-free remission. Adverse events were summarized for the TNF-naïve and TNF-failure subgroups by treatment received. RESULTS: Among patients who responded to vedolizumab induction at week 6, 48.9% of TNF-naïve and 27.7% of TNF-failure patients were in remission with vedolizumab at week 52 (versus 26.8% and 12.8% with placebo). Clinical efficacy was similar between the different types of TNF-α antagonist failure or the number of prior TNF-α antagonists failed. Safety profiles were similar in both subpopulations. CONCLUSIONS: Vedolizumab had increased efficacy over placebo in CD patients irrespective of TNF-α antagonist treatment history. Overall, rates of response and remission were numerically higher in patients receiving vedolizumab as a first biologic than in patients who had experienced TNF failure.
Keywords: udržovací chemoterapie; výsledek terapie; Tumor Necrosis Factor-alpha; Middle Aged; gastrointestinální látky; mužské pohlaví; Gastrointestinal Agents; Crohnova nemoc; Adult; indukční chemoterapie; TNF-alfa; ženské pohlaví; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; lidé středního věku; Crohn Disease; Induction Chemotherapy; Maintenance Chemotherapy; dospělí; Female; Treatment Outcome; lidé; Male